The (in)disputable 'power' of images of outrage: public acknowledgement, emotional reaction, and image recognition. (November 2019) - Dahmen, Nicole Smith; Mielczarek, Natalia; Morrison, Daniel D
A recent news image – that of a drowned 3-year-old Syrian boy washed ashore on the Turkish coast as a result of refugees fleeing the ongoing war in Syria – resonated with international audiences and world leaders, becoming a seeming catalyst for action. But, as time has shown, the effect was short-lived. Through survey data, this research explores iconic images and visual collective memory throughout history and into the era of digital news and social media. More specifically, the research considers connections between public acknowledgement, emotional reaction, and image recognition. Studying such relationships will help us to further understand the (in)disputable 'power' that famous photographs possess to imprint themselves onto people's minds, thus leading to supposed effect and action.